Value Added Tax: An Instrument used in some African Countries to Meet Fiscal Objectives - Chauke, K.R.; Sebola, M.P. (Journal of Reviews on Global Economics, 2019)
This article aims to evaluate the extent at which VAT is used as an instrument by countries to meet their fiscal deficit and meet the needs of their citizenry. Taxpayers pay taxes based on their ability to pay and with an anticipation that they will receive services in return to their contribution from government. The VAT due to its buoyancy nature contributes sizable amount of taxes which alleviate the financial burden of countries in meeting the financial obligations. Numerous kinds of literature demonstrate that whenever countries experience any budget shortfall they always look for fiscal remedies in either introduction of VAT or changing the rate of VAT. South Africa recently changed its long term rate of 14 % VAT to 15%. This article is conceptual in approach and uses the literature to argue that Value Added Tax (VAT) can be used as an effective instrument to meet fiscal objectives in some African Countries. Countries have the responsibility to ensure that their subject contributes to taxes which amongst others should in the form of VAT. As in the case of other taxes, the taxes are used to meet the fiscal obligation a country faces. The paper concludes that many countries that have introduced VAT have managed to meet their fiscal obligation due to high revenue contribution that have emanated from it, making the VAT the best tax methods to enable the country to meet their fiscal obligations.